Quantitative comparison of the effects of cholecystokinin, secretin, and pentagastrin on gastrointestinal myoelectric activity in the conscious fasted dog. Issue 7 (July 1978) - Wingate, D L; Pearce, E A; Hutton, M; Dand, A; Thompson, H H; Wünsch, E
Abstract : The effects on gastrointestinal myoelectric activity of infused pentagastrin, cholecystokinin (CCK), and secretin at physiological doses were studied in live dogs with implanted serosal electrodes during 56 six-hour studies. Pentagastrin dose-dependently increased gastric and duodenal slow-wave frequencies; secretin and CCK did not. Pentagastrin and CCK diminished the incidence of fasting migrating myoelectric complexes (MMCs), but MMCs were abolished only in the proximal small intestine. Pentagastrin infusion was not reflected in an increased number of spikes, whereas CCK induced a dose-dependent increase in jejunal spike activity. Secretin dose-dependently decreased duodenal and jejunal spike incidence without a marked effect on MMC incidence. Analysis of patterns of spike activity showed significant dose-dependent changes with all three peptides. The different effects of pentagastrin and CCK on spike activity in these studies may have been a consequence of pentagastrin-stimulated gastric acid secretion. None of the three peptides produced a pattern of myoelectric activity which closely resembled that seen on feeding; since, unlike food, all three peptides had little or no effect on the distal small intestine, it seems unlikely that combinations of these peptides are responsible for the change induced by food. The failure of these peptides to abolish fasting patterns in the distal intestine suggests a possible mechanism for some types of post-vagotomy dysfunction.